"New boys on the block" limited liability partnerships; Special reference to the LLP consultative document April 2008 - Abd Ghadas, Zuhairah Ariff (2009)
Partnerships structure has long been accepted as one of the major business vehicles. It is generally opted by small and medium businesses and by the professionals. With the development of the economy, the general partnerships structure was found to be no longer suitable for some of the businesses, particularly the professionals. The rising cost in trade and litigation has forced partners to take precaution as regards the extent of liabilities in the business. These lead to development in partnerships structure to limited partnership, limited liability partnerships, and incorporated limited liability partnerships. In Malaysia, the Companies Commission of Malaysia (CCM) had recently published the second consultation paper on Limited Liability Partnerships (LLP). As LLP is still an alien business structure in Malaysia, the consultation paper highlighted some of the important features of a LLP that differ it from the existing business vehicles. The consultation paper also marked the birth of change in Malaysian Partnership laws after nearly 35 years of settling with only the Partnerships Act 1961. This paper intends to discuss features of Malaysian LLP as proposed by the CCM and how the new LLP will affect businesses in Malaysia, particularly the partnerships structure.